Preliminary study on the agrotourism approach to sustain the local cultural landscape. A case study at Taman Warisan Pertanian Putrajaya - Mat Som, Mohd Shafiq; Mohd. Yaman, Maheran ([s.n.], 2011)
Human beings and nature have a mutual relationship in which human beings depend on nature for resources such as food, shelter, clothing and others. The history of mankind began with hunting activities which then evolved to an agricultural-based life. Local livestock breeds or plant varieties are designed to adapt the cultural landscape and creates a niche of different regions or places all over the world. In modern times, the agricultural-based activities are capitalized in rural culture where people still depend on livestock breeds and vegetation for food and farm marketing. The different climate, geography, landscape, population and culture create a diversity in terms of types and techniques of breeding and farming. Hence, it developed the local niche which attracts people from local and overseas to come and learn the culture of traditional farming that is different from one country to another. People have become more interested in how their food is production. They want to meet farmers and processors and talk with them about what goes into food productions. With the lifestyle changes from agricultural to industrial development in many parts of the world, farms seem to be one of the more popular places to be visited by tourists. This creates a new tourism activity called agrotourism in which the cultural landscape attracts people with agricultural-based operation or activities, i.e: that bring visitors to the farm and experience buying products from the farm stand, navigating a corn maze, picking fruits, feeding animals, or staying at a barn.